1999
DOI: 10.1177/074193259902000104
|View full text |Cite
|
Sign up to set email alerts
|

General Educators' Attitudes Toward Students with Mild Disabilities and Their Use of Instructional Strategies

Abstract: In today's schools the demands of general educators to meet the diverse needs of their students have greatly increased. General educators need to have an increasingly large repertoire of instructional strategies to effectively meet their students' needs. In this study the frequency of several instructional strategies used by general educators at the middle school level (Grades 6, 7, and 8) was investigated. The frequency of the use of these instructional strategies by middle school teachers was compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 15 publications
6
29
0
3
Order By: Relevance
“…A total of eight studies were located through this procedure for inclusion in this synthesis (DeBettencourt, 1999;DeSimone & Parmar, 2006;Fletcher, Bos, & Johnson, 1999;Leyser & Tappendorf, 2001;Maccini & Gagnon, 2006;Minke, Bear, Deemer, & Griffin, 1996;van Hover & Yeagar, 2003;Vaughn, Reiss, Rothlein, & Hughes, 1999). Findings were consistent with the previous synthesis (Scott et al, 1998) and revealed that teachers perceived the majority of instructional adaptations to be highly desirable and somewhat feasible, but reported being only fairly confident, prepared, and supported to implement instructional adaptations in their classroom.…”
Section: Studies To Determine the Effectiveness Of Instructional Adapsupporting
confidence: 53%
“…A total of eight studies were located through this procedure for inclusion in this synthesis (DeBettencourt, 1999;DeSimone & Parmar, 2006;Fletcher, Bos, & Johnson, 1999;Leyser & Tappendorf, 2001;Maccini & Gagnon, 2006;Minke, Bear, Deemer, & Griffin, 1996;van Hover & Yeagar, 2003;Vaughn, Reiss, Rothlein, & Hughes, 1999). Findings were consistent with the previous synthesis (Scott et al, 1998) and revealed that teachers perceived the majority of instructional adaptations to be highly desirable and somewhat feasible, but reported being only fairly confident, prepared, and supported to implement instructional adaptations in their classroom.…”
Section: Studies To Determine the Effectiveness Of Instructional Adapsupporting
confidence: 53%
“…Villa and Thousand (2000) claimed that inclusion is first an attitude, a value and belief system instead of an action. This statement was confirmed by a huge number of attitudinal studies (e.g., Coutinho and Repp, 1999;Debettencourt, 1999;Salend, 1998;Salisbury, 2006;Siperstein, Bardon and Widaman, 2007) revealing that positive attitudes of key school personnel are seen as critical prerequisites for successful inclusion. However, research results have also shown that attitudes of these personnel have often been differential or sometimes contradictory, and have often been selected by both proponents and opponents to support or oppose the inclusion movement (Padeliadu and Lampropoulou, 1997).…”
Section: Overview Of Inclusive Education Initiativesmentioning
confidence: 50%
“…Studies indicated that the key for forming positive attitudes among teachers lies in training them to work with such pupils (Hasazi et al , 1994;Debetterncourt, 1999;Avramidis, 2000;Avramidis et al , 2000). Allport et al (1960) found that emotional and behavioural changes among social workers, nurses and teachers were achieved when information about disabilities was provided (the cognitive component of attitudes), in addition to practical experience (the behavioural component).…”
Section: Teachers' Attitudes Towards Pupils With Special Needsmentioning
confidence: 97%